EU-Turkey Relations Theories, Institutions, and Policies - Reiners, Wulf; Turhan, Ebru (Springer Nature, 2021)
This open access book explores the new complexities and ambiguities that epitomize EU-Turkey relations. With a strong focus on the developments in the last decade, the book provides full access to a comprehensive understanding of the multifaceted relationship through three entry points: (1) Theories and Concepts, (2) Institutions, and (3) Policies. Part I brings together complementary and competing analytical approaches to study the evolution of EU-Turkey relations, ranging from traditional integration theories to novel concepts. Part II investigates the institutional machinery of EU-Turkey relations by analyzing the roles and perspectives of the European Council, the European Commission, and the European Parliament. Part III offers analyses of the policies most relevant for the relationship: enlargement policy, trade and macroeconomic policies, foreign and security policy, migration and asylum policies, and energy policy. In Part IV, the volume closes with a systematic survey of the conditions under which cooperative trends in EU-Turkey relations could be (re)invigorated. The systematic setup and the balanced combination of distinguished experts from EU- and Turkey-based institutions make this book a fundamental reading for students, researchers, lecturers, and practitioners of EU-Turkey relations, European integration and Turkish foreign policy.